Female sexual dysfunction and associated co-morbidities: a cross sectional study with Female Sexual Function Index (FSFI) in a tertiary care hospital of Bangladesh (Bangladesh Journal of Psychiatry, 2020)
Talks regarding sexual problems are not encouraging in Bangladesh and sufferers are in grave situation as they are not sure regarding whom to approach and how to start. It was aimed to see the presenting patterns of female sexual dysfunctions (FSD) and co-morbidities among the patients attending at different outpatient departments (OPD) at Bangabandhu Sheikh Mujib Medical University (BSMMU). This descriptive cross sectional study was conducted among 173 female patients attending at gynecology, endocrinology and psychiatry OPD, BSMMU. Sample was taken by convenient sampling within the period of October 2015 to December 2016. Data were collected through face-to-face interview with Female Sexual Function Index (FSFI) questionnaire. The results showed that, most (95.95%) of the patients were in the reproductive age group. Majority of the patients (32.95%) were in 26-30 years age group and 24.85% were in 18-25 years age group. Majority (77.5%) belonged to home maker occupational class where 12.7% was service-holder. Fifty six percent of the respondents were found to have sexual dysfunctions and 38.15% patients had endocrinological co-morbidities, 37.57% had gynecological co- morbidities and 33.53% had psychiatric co-morbidities. Positive openness in sexual health is required for the betterment of both treatment and diagnosis of sexual disorders. Specialized service center focusing the different groups is needed to deal with sexual health in a developing country like Bangladesh.Bang J Psychiatry December 2016; 30(2): 27-31